Financování podnikatelských aktivit - Svrčková, Mária (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Bakalárska práca sa zaoberá financovaním dlhodobého majetku výrobnej firmy Sonnentor. Práca je rozdelená na teoretickú, analytickú a návrhovú časť. V teoretickej časti sú vymedzené základné teoretické východiska, ako zdroje financovania a analýza stavu podniku. V analytickej časti sú následne vykonané jednotlivé analýzy podniku. Podstatou práce je navrhnutie najvhodnejšieho spôsobu financovania plánovanej investície.

The bachelor thesis deals with the financing of fixed assets of the manufacturing company Sonnentor. The thesis is divided into theoretical, analytical and proposal part. The theoretical part defines the basic theoretical background, such as sources of financing and an analysis of the state of the company. In the analytical part, individual analysis of the company are subsequently carried out. The essence of the thesis is to recommend the most effective way of financing the planned investment.
Financing of business activities
Keywords: zdroje financovania; dlhodobý majetok; SWOT; SLEPT analýza; Porterova analýza; sources of financing; fixed assets; SWOT; SLEPT analysis; Porter's five forces analysis